Aktivitas Antidiabetes Ekstrak Etanol Daun Bidara Pada Tikus Dengan Induksi Streptozotocin - Wahyuni, Kumala Sari Poespita Dewi; Mawardika, Herlinda; Sabban, Indra Fauzi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Type 2 Diabetes Mellitus is a global health problem that continues to increase, requiring safer and more effective alternative therapies. Bidara leaves have been known to have bioactive compounds that are useful as antioxidants, antimicrobials, and antidiabetics. This study aims to determine the potential of bidara leaf extract in lowering blood sugar in diabetic rats. This study is an experimental research with four treatments. This study includes the manufacture of bidara leaf extract through the maceration method, phytochemical screening, and testing of antidiabetic activity in STZ-induced animal models. Blood sugar levels were measured before and after the intervention. The results showed that (1) bidara leaf extract contains flavonoids, tannins, saponins, steroids, and quinones; (2) Giving extracts with various concentrations for 42 days can reduce blood glucose levels in rats; (3) Bidara leaf extract at a dose of 400 mg/ml showed higher activity than other doses. Thus, it can be concluded that 70% ethanol extract of bidara leaves can be used to treat type 2 diabetes mellitus.